Molecular Docking Analysis of Berberis aristata Phytocompounds as Potential Growth Factor Receptor Blockers in Cancer Therapy - Sivakumarreddy Bapatu (International Journal of Cell Biology and Cellular Functions, 2025)
Middle-aged and older women are susceptible to breast cancer (BC), a potentially fatal condition. When breast cancer is diagnosed, the median age is 62. Breast cancer diagnoses in women under 45 are comparatively uncommon, whereas the bulk of breast cancer diagnoses occur in women 62 and older. Growth factor receptors are interesting therapeutic targets because of their critical role in the pathophysiology of cancer. Vascular endothelial growth factor receptors (VEGFR-2) and human epidermal growth factor receptors (HER-2) have a role in the development and spread of cancer. To determine their HER-2 binding affinity, 39 phytocompounds from Berberis aristata were chosen. PyRx, a virtual screening tool, was used for molecular docking. Databases including PubChem, Indian medicinal plants, phytochemistry, and therapeutics were used to obtain the molecular structures of the compounds and the targeted proteins. Protein Data Bank sum generation and BIOVIA Discovery Studio tools were used to validate the protein structures. Additionally, ADMET was used to assess the ligands’ pharmacokinetic characteristics.
Keywords: ADMET analysis; Berberis aristata (BA); Breast cancer (BA); Human epidermal growth factor receptors (HER-2); molecular docking